ANALISIS KOMPENSASI KARYAWAN PADA BENGKEL ZUMA MOTOR PASIR PENGARAIAN - Hidayat, Iwan (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Compensation is the remunerationprovided by the organization / company tothe employees, which may be financial ornon-financial, in a fixed period. This studyaims to determine the types ofcompensation of employees in the garageZuma Motor Pasir Pengaraian and analyzethe factors that affect employeecompensation Zuma Motor PasirPengaraian workshop.This study used a qualitative approach,types and sources of data used arequalitative data and quantitative data. Datasources include primary data collectionand data sekunder.Teknik data usingobservations, interviews andquestionnaires.The results showed that the type ofcompensation received by employees whowork on the Workshop Zuma Motor PasirPengaraian is financial compensation andnon-financial compensation. Based on theresults of the study revealed thatemployees basically assume that thecompensation received by the employee isable to say